2020
DOI: 10.3390/en13082080
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation Ability of Mg-Li Alloys

Abstract: The Mg-Li binary system is characterized by the presence of α-Mg(Li) and β-Li(Mg) phases, where magnesium exists in ordered and disordered forms that may affect the hydrogenation properties of magnesium. Therefore, the hydrogenation properties of an AZ31 alloy modified by the addition of 4.0 wt.%, 7.5 wt.% and 15.0 wt.% lithium were studied. The morphology (scanning electron microscopy (SEM)), structure, phase composition (X-ray diffraction (XRD)) and hydrogenation properties (differential scanning calorimetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The most popular metal catalysts are transition metals, e.g., Al, Fe, Cu, Pd, Ni, V, Nb, Ti, Mn, and Cr (synthesized together with Mg by BM and RBM techniques) [ 85 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 ]. However, recently, some alkali metals have also been used [ 105 ]. Vitorri Antisari et al [ 93 ] showed a correlation between experimental results and a model describing the role of Fe catalyst particles in the nucleation step in the MgH 2 reaction.…”
Section: Magnesium Hydridementioning
confidence: 99%
“…The most popular metal catalysts are transition metals, e.g., Al, Fe, Cu, Pd, Ni, V, Nb, Ti, Mn, and Cr (synthesized together with Mg by BM and RBM techniques) [ 85 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 ]. However, recently, some alkali metals have also been used [ 105 ]. Vitorri Antisari et al [ 93 ] showed a correlation between experimental results and a model describing the role of Fe catalyst particles in the nucleation step in the MgH 2 reaction.…”
Section: Magnesium Hydridementioning
confidence: 99%
“…This system has a higher hydrogen storage density of 6.5 H atoms/cm 3 for MgH 2 when compared with pure hydrogen gas (0.99 H atoms/cm 3 ) or liquid hydrogen (4.2 H atoms/cm 3 ). Mg metal has various advantages for hydrogen storage, including low cost, light weight, and high gravimetric (7.60 wt%) and volumetric (110 g/L) hydrogen storage capacities [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. In spite of the attractive and useful properties of Mg/MgH 2 , there are some serious drawbacks that should be solved before using this system for FC-hydrogen storage applications.…”
Section: Introductionmentioning
confidence: 99%